(untitled) (London Journal of Medical and Health Research, 2023)
BACKGROUND: Venous thrombosis of the lower limbs, with the thrombo-embolic complications that can derive from it, constitutes a potentially fatal disease, for which an ultrasound examination, which today represents the diagnostic method recognized as a gold-standard in venous pathology, performed the most rapidly possible is capable of reducing the morbidity and mortality associated with the acute thrombotic event, the incidence of relapses and distant sequelae. METHODS: The purpose of this study is to report and analyze the experience gained over ten years on patients sent to the emergency department of reference for the area with the presumed diagnosis of deep or superficial vein thrombosis of the lower limbs. From March 2001 to December 2011, 30350 patients were examined as an emergency; all underwent an accurate medical history, for the evaluation of the Wells score, and venous Doppler ultrasound examination of the lower limbs, with detailed CUS technique, only on the affected lower limb. RESULTS: A positive diagnosis for acute phlebopathy in progress of patients undergoing urgent instrumental assessment, with detailed unilateral CUS technique, was detected in 7400 cases, which specifically concerned the deep tract more than the superficial one. The therapy was obviously diversified according to the pathology detected. CONCLUSIONS: Based on the clinical experience conducted, it is clear that the thrombo-embolic pathology was found only in about a quarter of the cases sent to the specialist doctor, of which only a small number of patients needed hospitalization.